Kawasaki disease: a prospective population survey in the UK and Ireland from 2013 to 2015 - Tulloh, R; Mayon-White, R; Harnden, A; Ramanan, A; Tizard, E; Shingadia, D; Michie, C; Lynn, R; Levin, M; Franklin, O; Craggs, P; Davidson, S; et al. (BMJ Publishing Group, 2018)
Objective: Kawasaki disease (KD) is an increasingly common vasculitis with risk of coronary artery aneurysms (CAAs). The last UK survey was in 1990, whereas current epidemiology, treatment patterns and complication rates are unknown. The aim of this study was to address this knowledge gap. Methods: A British Paediatric Surveillance Unit survey in the UK and Ireland from 1 January 2013 to 28 February 2015 ascertained demographics, ethnicity, seasonal incidence, treatment and complication rates. Results: 553 cases were notified: 389 had complete KD, 46 had atypical KD and 116 had incomplete KD; 2 were diagnosed at postmortem with an incidence of 4.55/100 000 children under 5 years, with a male to female ratio of 1.5:1 and a median age of 2.7 years (2.5 months–15 years). Presentation was highest in January and in rural areas. Most were white (64%), and Chinese and Japanese Asians were over-represented as were black African or African mixed-race children. 94% received intravenous immunoglobulin (IVIG). The overall CAA rate was 19%, and all-cardiac complications affected 28%. Those with CAA received IVIG later than in those without (median 10 days vs 7 days). Those under 1 year had fewer symptoms, but the highest CAA rate (39%). Overall 8 of 512 cases (1.6%) had giant CAA, and 4 of 86 cases (5%) under 1 year of age developed giant CAA. Mortality from KD was 0.36%. Conclusions: The UK and Ireland incidence of KD has increased and is more frequently seen in winter and rural areas. Delayed IVIG treatment is associated with CAA, suggesting earlier and adjunctive primary treatment might reduce complications to prevent CAA, particularly in the very young.